L’appartement périurbain : une place choisie ? Politiques de densification des bourgs en Île-de-France et modes d’habiter périurbain - Claire Fonticelli (Territoire en Mouvement, 2021)
Densification is an objective of public policies in France. It has consequences on the urban forms: apartments buildings are built in peri-urban areas. It is a break with the most common habitat in these municipalities: the single-family house. How do the peri-urban inhabitants live in an apartment in these spaces? What are the social representations that they associate to the peri-urban apartments? If individual housing is a norm in peri-urban areas, what is the "place" of the inhabitants of collective housing? Do they choose the apartment or want a detached house that they cannot get? Has this new "place" come to recompose their way of living? We did a survey among residents of new apartments in various peri-urban municipalities. There are three profiles of inhabitants. Those for whom the apartment is chosen, those who live there for a limited time, and those who live in an apartment to live in the suburbs, but still dream of a detached house.